2018
DOI: 10.1016/j.jneumeth.2017.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning reveals Alzheimer's disease onset in MCI subjects: Results from an international challenge

Abstract: DNNs reach a classification accuracy significantly higher than other machine learning strategies; on the other hand, fuzzy logic is particularly accurate with cMCI, suggesting a combination of these approaches could lead to interesting future perspectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(55 citation statements)
references
References 29 publications
1
54
0
Order By: Relevance
“…However, the different data, processes, assessment and classification techniques used do not always allow a completely fair comparison. This is why it is important to organize International challenges [ 12 , 31 ] to validate different methodologies with a common set of data and evaluation procedures. Apart the differences due to the previously enclosed reasons, in Table 3 it can be observed that our performances are comparable with the state-of-the-art [ 32 , 33 ] although the optimization of the diagnostic accuracy was not the primary goal of this work.…”
Section: Discussionmentioning
confidence: 99%
“…However, the different data, processes, assessment and classification techniques used do not always allow a completely fair comparison. This is why it is important to organize International challenges [ 12 , 31 ] to validate different methodologies with a common set of data and evaluation procedures. Apart the differences due to the previously enclosed reasons, in Table 3 it can be observed that our performances are comparable with the state-of-the-art [ 32 , 33 ] although the optimization of the diagnostic accuracy was not the primary goal of this work.…”
Section: Discussionmentioning
confidence: 99%
“…Deep neural networks (DNNs) are commonly used to classify data in different fields (LeCun et al, 2015 ; Amoroso et al, 2018 ; Wang et al, 2018 ). DNNs are non-linear methods that allow the learning of complex patterns among features, thus providing a complex non-linear classification of input data (Graepel et al, 2010 ).…”
Section: The Application Of Deep Learning Methods In Psychologymentioning
confidence: 99%
“…Different machine learning methods, such as the random forest algorithm, allow researchers to find best features/variables to explain differences among two or groups of participants (Amoroso et al, 2018 ). There are several ways to conduct feature selection.…”
Section: The Application Of Deep Learning Methods In Psychologymentioning
confidence: 99%
“…Developing computer aided diagnosis systems is desirable, as they can provide a non-invasive, low-cost tool-support to the traditional neuropsychological assessment performed by expert clinicians. Moreover, a great variety of state-of-the-art machine learning approaches, has shown outstanding performance for early detection and automated classification of Alzheimer's disease (AD) [12,13].Recently, we investigated the usefulness in this context of an uncommon graph measure, that is communicability. Communicability quantifies the ease of communications between node pairs in a network by considering not only the shortest path connecting them, but all possible available routes [14].…”
mentioning
confidence: 99%
“…Developing computer aided diagnosis systems is desirable, as they can provide a non-invasive, low-cost tool-support to the traditional neuropsychological assessment performed by expert clinicians. Moreover, a great variety of state-of-the-art machine learning approaches, has shown outstanding performance for early detection and automated classification of Alzheimer's disease (AD) [12,13].…”
mentioning
confidence: 99%